2009
DOI: 10.1590/s1516-35982009000600021
|View full text |Cite
|
Sign up to set email alerts
|

Fontes de energia em suplementos múltiplos para recria de novilhos mestiços em pastejo durante o período de transição seca/águas: desempenho produtivo e características nutricionais

Abstract: Energy sources in multiple supplements for growing crossbred steers on pasture during the dry to rainy seasons: performance and nutritional characteristics ABSTRACT -This study was conduced to evaluate the energy sources, rich in starch or fiber in multiples supplements on performance and nutritional characteristics of finishing crossbred steers in the dry/rainy transition season, grazingBrachiaria decumbens Stapf. The experimental area was divided into 5 paddocks with 2.0 ha each, with dry matter availability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
2
0
4
Order By: Relevance
“…For every 1 kg of protein supplement ingested, there was a 60% increase in microbial protein synthesis compared with control. Nascimento et al (2009), when working with crossbred steers supplemented with 0.4% BW (30% CP) during the 1 S = non-supplemented versus supplemented; NS = nitrogen salt versus multiple supplementation; L and Q = linear and quadratic order effects on multiple supplementation levels, which involves only information from levels of multiple supplement; 2 / (ns), (*), (**) and (***) = non-significant (P>0.10) and significant at the levels of 0.10, 0.05 and 0.01 of probability by the F test, respectively; 3 calculated by equation proposed by Detmann et al (2006) Table 6 -Least square means for apparent digestibility dry-rainy transition period, observed that the supplemented animals obtained Nmic production 34.4% higher than the control animals. A similar behavior was observed in this study, in which for the estimated level of multiple supplement (45% CP) OF 0.4% BW (800 g/day), 48% of production superiority was found in Nmic production when compared to control animals.…”
Section: Methodsmentioning
confidence: 99%
“…For every 1 kg of protein supplement ingested, there was a 60% increase in microbial protein synthesis compared with control. Nascimento et al (2009), when working with crossbred steers supplemented with 0.4% BW (30% CP) during the 1 S = non-supplemented versus supplemented; NS = nitrogen salt versus multiple supplementation; L and Q = linear and quadratic order effects on multiple supplementation levels, which involves only information from levels of multiple supplement; 2 / (ns), (*), (**) and (***) = non-significant (P>0.10) and significant at the levels of 0.10, 0.05 and 0.01 of probability by the F test, respectively; 3 calculated by equation proposed by Detmann et al (2006) Table 6 -Least square means for apparent digestibility dry-rainy transition period, observed that the supplemented animals obtained Nmic production 34.4% higher than the control animals. A similar behavior was observed in this study, in which for the estimated level of multiple supplement (45% CP) OF 0.4% BW (800 g/day), 48% of production superiority was found in Nmic production when compared to control animals.…”
Section: Methodsmentioning
confidence: 99%
“…Prolamin, a protein in the maize grain that wraps starch granules, is another factor that may jeopardize starch granules in cereals (Chandrashekar & Mazhar, 1999). The protein occurs in the endosperm (30 -60% of total grain protein) and envelops and turns impervious starch granules in a hydrophobic matrix, making difficult the access of microorganisms and their enzymes in the granule (Nascimento et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Não houve efeito (P>0,05) da suplementação no nitrogênio uréico no plasma (NUP). Os níveis variaram entre 10,58 e 16,70 mg/dL, e estão dentro dos valores encontrados na literatura com gado de corte pastejando forrageiras tropicais (NASCIMENTO et al, 2009;NASCIMENTO et al, 2010;MORAES et al, 2009). Magalhães et al (2005) Os valores de lag time, DE, c e I obtidos neste trabalho foram semelhantes aos encontrados por Danés (2010), que ao avaliar as mesmas variáveis para o capim Elefante, relatou valores entre 4,8 e 6,4 (lag time), 47% (DE a 2%/h), 4,4 e 5,0 (c) e 20% (I).…”
Section: Excreção De Nitrogênio Síntese De Proteína Microbiana E Nitunclassified
“…Porém no que se referem à degradabilidade potencial, os valores encontrados neste estudo, apresentam-se mais elevados do que os encontrados por alguns autores (DANÉS, 2010;CARVALHO et al, 2008;OLIVEIRA et al, 2010) 2001; Sales et al (2008aSales et al ( , 2008b; Nascimento et al (2010Nascimento et al ( , 2009; Lardy et al 2004 4.7 Cinética de fermentação ruminal in vitro "gás"…”
Section: Excreção De Nitrogênio Síntese De Proteína Microbiana E Nitunclassified